The Funeral Achievements of Henry V at Westminster Abbey : The Arms and Armour of Death. - Curry, Anne.; Jenkins, Susan; Capwell, Toby.; Edge, David; Given-Wilson, Christopher; Goodall, John.; Hill, Robert; Heath, Diana; Monnas, Lisa.; Woosnam-Savage, Bob. (Woodbridge : Boydell & Brewer, Incorporated, 2022)
Ground-breaking new studies of Henry V's chapel, tomb and funeral service have new revelations and insights into the time.
Description based upon print version of record.
JSTOR
Keywords: Henry -- V, -- King of England, -- 1387-1422 -- Death and burial; Henry -- V, -- King of England, -- 1387-1422 -- Tomb; Westminster Abbey; Henry -- V, -- King of England, -- 1387-1422; Westminster Abbey; Death and burial of a person; Tombs